HUBUNGAN KEBIJAKAN KRIMINAL DENGAN KEBIJAKAN HUKUM PIDANA - Febriyanti Silaen; Syawal Amry Siregar (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2020)
The problem of overcoming crime in the community cannot be separated from the word Criminal policy which is carried out in the efforts of criminal policy and political policy. The relationship of criminal policy with criminal law policy is equally tackling crime where one is, by means of a penal effort while the difference is with non-criminal words or with the enforcement system only, if the criminal policy uses the word criminal justice system, with some crime prevention and handling by means of Penalty has several stages: Formulation (Legislative Policy), Application (Judicial or Judicial Policy); Execution (Executive Policy). Criminal countermeasure policy is the same as criminal law policy, which is protecting society to achieve social welfare. The effectiveness of criminal sanctions can be an important aspect to support the achievement of the criminal policy.